2020
DOI: 10.1063/1.5145303
|View full text |Cite
|
Sign up to set email alerts
|

Capillary flow of sodium and zinc ionomers

Abstract: The capillary flow properties of several commercial ionomers (sodium and zinc) were studied to assess their processability in terms of instabilities such as wall slip and melt fracture. Using capillary dies of various diameters and lengths to control capillary extrusion pressure, it was found that the viscosity of these polymers exhibits a relatively small dependence on pressure, more importantly at relatively smaller pressures. Using capillaries of various diameters at fixed length-to-diameter ratios, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The importance of the extensional viscosity on the entry pressure was studied extensively for the case of ionomers [ 40 , 41 , 42 , 43 ]. Results are presented in Figure 3 for two polymers, one ionomer (19.2-Na65) and its corresponding copolymer (19.2-Na65).…”
Section: Capillary Rheometrymentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of the extensional viscosity on the entry pressure was studied extensively for the case of ionomers [ 40 , 41 , 42 , 43 ]. Results are presented in Figure 3 for two polymers, one ionomer (19.2-Na65) and its corresponding copolymer (19.2-Na65).…”
Section: Capillary Rheometrymentioning
confidence: 99%
“…Unlike Newtonian fluids, polymer melts slip over solid surfaces when the wall shear stress exceeds a critical value [ 13 , 14 , 15 , 16 , 17 , 18 ]. In particular, slip effects have been reported in the capillary flow of molten polyethylenes [ 44 , 45 , 46 , 47 , 48 , 49 ], polydimethylsiloxanes [ 50 ], polystyrenes [ 51 , 52 , 53 ], polybutadienes [ 54 , 55 ], polypropylenes [ 56 , 57 , 58 ], fluoropolymers [ 59 ], polylactides [ 60 ], polyisobutylenes [ 61 ], ionomers [ 40 , 41 ] and other viscoelastic fluids [ 62 , 63 ]. Thus, in a comprehensive study of any melt, possible slip effects should be studied to be used as boundary conditions in high shear rate flows.…”
Section: Slip Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the flow behaviour of viscoelastic fluids in confined geometries is essential for applications in polymer melt/solution processing [1][2][3][4], processing of biological/medical systems [5][6][7], enhanced oil recovery [8][9][10], dampers [11][12][13] and many others. Historically, Tordella [14] in 1957 was the first to attempt to visualize the die entry flow region during his original work on melt fracture research.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these highly elastic systems exhibit melt fracture phenomena that manifest themselves as distortions on the surface of extruded TPV samples. [ 31 ] While several melt fracture studies exist for polymer melts such as polyethylenes, [ 32‐34 ] polypropylenes, [ 35,36 ] polystyrenes, [ 37 ] polydimethylosiloxanes, [ 38 ] polylactides and polycaprolactones, [ 39‐41 ] fluoropolymers, [ 42 ] polybutylenes, [ 43 ] ionomers [ 44 ] as well as polymer blends and composites, [ 45‐48 ] specific studies focused on TPVs are rare. The single study by Wu et al [ 31 ] on TPV melt fracture reported that by increasing the time of TPV extrusion via performing the extrusion twice and with increasing the extrusion temperature, more smooth extrudate surfaces are achieved.…”
Section: Introductionmentioning
confidence: 99%